2008
DOI: 10.1016/j.eurpsy.2008.01.1060
|View full text |Cite
|
Sign up to set email alerts
|

Abuse of Tianeptine: A case report

Abstract: The objective of the authors is to make a reflection about the causes of tianeptine abuse and dependence. In the scientific literature we can find case studies of anti-depressive dependence, which show amphetaminergic effects. In what concerns other anti-depressives, the information is rare, specifically about tianeptine. The few case studies reported until now, focus the psychostimulant effect as being the cause of the abuse and dependence. Though, a study case is described of a female patient, with 40 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In a study of Ferreira et al (15) they identified a 40-year-old woman who had a history of alcohol depend-ence and consumed about 10 coffees and 40 cigarettes a day. The patient said that she used tianeptine for many years and was admitted to a psychiatric ward 3 times in the last 6 months because they used a higher dose (1286 mg per day).…”
Section: Resultsmentioning
confidence: 99%
“…In a study of Ferreira et al (15) they identified a 40-year-old woman who had a history of alcohol depend-ence and consumed about 10 coffees and 40 cigarettes a day. The patient said that she used tianeptine for many years and was admitted to a psychiatric ward 3 times in the last 6 months because they used a higher dose (1286 mg per day).…”
Section: Resultsmentioning
confidence: 99%